Examination of uropathogenic Escherichia coli strains conferring large plasmids - SUHARTONO SUHARTONO (Society for Indonesian Biodiversity, 2010)
Suhartono (2010) Examination of uropathogenic Escherichia coli strains conferring large plasmids. Biodiversitas 11: 59-64. Of major uropathogens, Escherichia coli has been widely known as a main pathogen of UTIs globally and has considerable medical and financial consequences. A strain of UPEC, namely E. coli ST131, confers a large plasmid encoding cephalosporinases (class C Î²-lactamase) or AmpC that may be disseminated through horizontal transfer among bacterial populations. Therefore, it is worth examining such large plasmids by isolating, purifying, and digesting the plasmid with restriction enzymes. The examination of the large plasmids was conducted by isolating plasmid DNA visualized by agarose gel electrophoresis as well as by PFGE. The relationship of plasmids among isolates was carried out by HpaI restriction enzyme digestion. Of 36 isolates of E. coli ST 131, eight isolates possessed large plasmids, namely isolates 3, 9, 10, 12, 17, 18, 26 and 30 with the largest molecular size confirmed by agarose gel electrophoresis and PFGE was 42kb and 118kb respectively. Restriction enzyme analysis revealed that isolates 9, 10, 12, 17 and 18 have the common restrictionpatterns and those isolates might be closely related.Key words: large plasmids, uropathogenic E. coli, electrophoresis, RE, PFGE